Behavior of Steel Plate Girders with Web Openings Loaded in Shear - May J. Hamoodi; Marwa S. Abdul Gabar (Engineering and Technology Journal, 2013)
The structural behavior of three steel plate girders under shear is studied. The first one is the reference plate girder (G) which is prepared without web openings, and the second one (GO) is fabricated to contain circular opening at the center of each web panel, the diameter of the opening is 60% of the web depth, while the third plate girder (GOR) is with reinforced strip welded around the circular web openings. The aspect ratio of the panels is one and they all have the same dimensions. The experimental results obtained from second and third plate girders have been compared with those obtained from the reference plate girder. The comparison indicates that the reduction in the ultimate shear load for plate girder with web opening is 51% and for the plate girder with reinforced web opening is 35%. Also through the experimental results, new formulas are presented to predict the ultimate shear load of perforated steel girders with large openings. A nonlinear finite element analysis is carried out for the tested plate girders using the package software program (ANSYS V.11). The analytical results contain the ultimate shear capacity and Von Mises stress distribution. The results of finite element models are compared with results of experimental tests. The difference in ultimate shear load was 10%, 9% and 1.5% for plate girders GO, GOR and G, respectively. Also a parametric study with varying size of the reinforcement around the web openings is performed by using the ANSYS program, and it is found that the thickness of the reinforcement strip has higher effect than its width on the ultimate shear capacity of perforated plate girder.